Guatemala - Country Note on Climate Change Aspects in Agriculture - World Bank (Washington, DC, 2012)
This country note briefly summarizes information relevant to both climate change and agriculture in Guatemala, with focus on policy developments (including action plans and programs) and institutional make-up. Like most countries in Latin America, Guatemala has submitted one national communication to the United Nations Framework Convention on Climate Change (UNFCCC). Land use change and forestry are by far the largest contributors to greenhouse gases (GHG) emissions in the country. The emission reduction potential of the sector is large, but not sufficiently explored. Guatemala counts with eight CDM projects, one of which is in the agricultural sector. It is estimated that Central America produces less than 0.5 percent of global carbon emissions, but it is one the most vulnerable regions to climate change related impacts on the planet. Agriculture is highly vulnerable to climate variability and weather extremes, this coupled with problems of land degradation in the country. A greater emphasis on reducing soil degradation, reforestation and developing and applying adequate insurance mechanisms can be placed for better management of public resources in light of natural disasters in the agriculture sector.